23 The first description of a smartphone-based evaluation of the conjunctival microcirculation in patients presenting with acute myocardial infarction. (30th September 2020) - Brennan, PF; Awuah, A; Jing, M; McNeil, A; Finlay, D; McLaughlin, J; Nesbit, MA; Trucco, E; Moore, T; Spence, MS
Abstract : Background: Microcirculatory dysfunction and microvascular dysfunction occur early in the development of cardiovascular disease (CVD) with acute myocardial infarction (MI) being a late consequence of CVD. The conjunctival microcirculation is readily-accessible for quantitative assessment using a slit-lamp biomicroscope. We have previously reported the study of the conjunctival microcirculation in healthy volunteers and in patients with cyanotic congenital heart disease. Methods: We performed conjunctival microcirculatory assessment in a group of inpatients with acute type 1 MI and in age/sex-matched healthy controls. Image acquisition and video capture was performed using an iPhone 6s combined with a slit-lamp biomicroscope. The conjunctival vessels in each hemisphere (temporal/nasal) of both eyes were studied. Microcirculatory parameters quantified included axial velocity, wall shear rate and blood volume flow. Results: Conjunctival microcirculatory assessment was assessed in 59 MI patients (mean age 57±12years, 80% male) and 56 healthy controls (mean age 53±10years, 68% male, mean QRISK-3 score 8.1±7.6%). STEMI and NSTEMI made up 36% (n=21) and 64% (n=38) of the MI patient group, respectively. Baseline characteristics are summarised in table 1 . A total of 4163 vessel segments (healthy control 1904 total, 34 per patient vs. MI 2259 total, 38 per patient) were analysed for the two groups. Mean conjunctival microvessel diameter was 21.41±7.57um for the controls which was significantly lower than the 22.32±7.66um seen in MI patients (p<0.0005). Axial velocity for the MI patients was significantly lower at 0.49±0.17mm/s compared to 0.53±0.15mm/s for the controls (p<0.0005 (figure 1 )). Wall shear rate was also significantly lower in the MI group (144.96±88.45s-1 vs. 162±93s-1, p<0.0005 (figure 2 )). There was no significant difference in blood volume flow between the MI and controls (154±124.8pl/s vs. 152.6±124.4pl/s, p 0.84). Conclusions: Using our novel imaging system, alterations in conjunctival microcirculatory parameters for MI patients compared to healthy controls were found. Axial velocity and wall shear rate were significantly lower in the MI group, similar to what we previously reported in patients with cyanotic congenital heart disease. These alterations in conjunctival microcirculatory parameters are suggestive of endothelial dysfunction and application of this system may enhance future assessment of CVD risk.